EFFECT OF DRAINAGE AND IRRIGATION METHODS ON PERFORMANCE OF SOYBEAN AND WHEAT CULTIVARS - Maurya, B.M. (Journal of Soil and Water Conservation, 2022)
Study on effect of drainage and irrigation tnethods on performance of Soybean and wheat eultivars was taken at Agri! Research farm Powarklioda during 1997-98. Soybean yield was increased by 27.57% due to provision of surface drainage as compared to .1 S72 -280 gave maximum grain yield 16.7 q/ha which was 16.05% more as compared to JS76-205. Among different varieties of wheat GW 173 gave more field *25.87q/ha) than Lok-1 (23.3701a). Irrigation through wells and tubewell was more efficient than Canal irrigation in wheat which gave 14.51% more yield. Effect of surface drainage was found effective to increase the yield of Wheat by 17.22% as compared to without drainage. The border strip irrigation was effective against uncontrolled flooding and gave 15.08% more yield of wheat-crop.